Jamal Alkinayat fi Alfarayid Alqurania - taha , hussein (Islamic Sciences Journal, 2023)
The importance of the current study stems from revealing the sects of the Quranic nicknames، which try to explore some of the rhetorical secrets in the Quranic euphemism، and through the unique words that the Holy Qur'an used to refer to، which he called: (the aesthetic aesthetics in the Qur’anic uniqueness) and The fun of the study lies in combining the two terms (Al-Fareed)، which the rhetoric counted as eloquence، and between (the metonymy)، which is one of the topics of the science of statement، stems from these unique words in touching the aesthetics of the Quranic metonymy، and through the application study of some of the verses that contain the words of the terminology can not be blocked by others because of their rarity It is like a unique love The contract is in its beauty، kindness، and elegance، and is taught through the wire of systems، and the relationship of the word to its neighborhood، and even through the context of the set of verses in which the verse is contained within it، and sometimes it goes beyond the necessity of the place for the surah، So that the reader finally reaches the rhetorical meaning in the metonymy and this is Meaning of the meaning.